2010
DOI: 10.1083/jcb.201004129
|View full text |Cite
|
Sign up to set email alerts
|

Lipid activation of the signal recognition particle receptor provides spatial coordination of protein targeting

Abstract: Phospholipid binding leads to accelerated assembly of the bacterial SRP receptor FtsY and SRP, allowing cargo proteins to be delivered to target membranes more efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
86
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(95 citation statements)
references
References 51 publications
(107 reference statements)
9
86
0
Order By: Relevance
“…The interaction of FtsY with lipids and the lipid-induced conformational change of the MTS are nucleotide-independent, indicating that lipid association of FtsY via its MTS is independent from its GTPase cycle. The recently shown predominant membrane association of FtsY supports this idea (6), while another study suggests that SRP facilitates the lipid association of FtsY (14).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The interaction of FtsY with lipids and the lipid-induced conformational change of the MTS are nucleotide-independent, indicating that lipid association of FtsY via its MTS is independent from its GTPase cycle. The recently shown predominant membrane association of FtsY supports this idea (6), while another study suggests that SRP facilitates the lipid association of FtsY (14).…”
Section: Discussionsupporting
confidence: 58%
“…However, the A domain is not essential in Escherichia coli as a truncation variant (termed NGϩ1) is functional in vivo (11). It was shown that the FtsY GTPase is activated by anionic phospholipids (9) and that the membrane interaction of FtsY is crucial for the release of RNCs from the SRP-FtsY complex (12,13), which was confirmed recently (14). Membrane interaction of E. coli FtsY depends on a conserved motif at the N terminus of the N domain, referred to as membrane-targeting sequence (MTS) (15).…”
mentioning
confidence: 62%
“…However, the identified interactions probably do not dictate docking of the receptor (13). In direct support of a functional interaction between FtsY and lipids, our recent studies revealed that the receptor contains a short and conserved lipid-binding amphipathic ␣-helix at the N-terminal edge of the N domain, which affects the enzymatic behavior of FtsY upon interaction with lipids (13,14), and recent studies further confirmed our conclusions (15). Modeling of the lipid-binding helix of FtsY and its similarity to the MinD membrane targeting sequence (14,16) suggest that the short helix interacts with acidic lipids, as proposed previously (11).…”
supporting
confidence: 72%
“…GTP (guanosine 5′-triphosphate)-driven rearrangements then bring the G domains of both proteins into close contact, giving a stable closed complex (36,37). This rearrangement also exposes a membrane-binding helix of FtsY and thus is coupled to the membrane targeting of cargo (38). Importantly, SRP•FtsY assembly contributes extensively to the fidelity of SRP (39).…”
mentioning
confidence: 99%